Ensaios do íntimo no cinema de Naomi Kawase - Souza, Kleverton de Almeida (2022)
This dissertation aims to investigate the work of the Japanese filmmaker Naomi Kawase(1969-), discussing the idea of intimacy and its relationship with the essayistic andselfreflexive practices in her cinematography. For this purpose, it is based, in the theoretical-conceptual scope, on the researches of Michel Foucault (1984, 2004), Gilles Deleuze(2005)and Timothy Corrigan (2015), among others, that support a study of three filmessays bythedirector: Katatsumori (Katatsumori - 1994), Birth/Mother (Tarachime - 2006) andTrace(Chiri - 2012). The questions that leadsthe research include understanding what complicationsinvolve the transposition of a subjective experience to a public sphere, or yet, inwhat waythe filmmaker uses cinema to expose her ideas and perspectives of the world. Withthese, weseek to observe if there is a dance between the self and the other that brings us closer toboththe characters and the director herself, whether through the proximity of the cameraorbysharing intimacy.